Metaverse-supply chain and halal behavior: bibliometric analysis, framework and implications - Fernando, Yudi; Eing, Gaik Chin; Wahyuni-Td, Ika Sari (Emerald Publisher, 2025)
Purpose: This paper aims to review how the metaverse influences and contributes to the halal industry, particularly focusing on halal logistics (HL), halal supply chain management (HSCM) and consumer behavior. Design/methodology/approach: This paper analyzed scholarly studies to investigate existing literature and current as well as future trends in the adoption of the metaverse in HL, supply chains and consumer behavior. The study explores the thematic structure of the current knowledge landscape, identifies research gaps and highlights potential directions for future research at the intersection of the metaverse, supply chain and halal behavior. The authors identified 286 papers that examined the integration of the metaverse with HL practices, supply chain management strategies and consumer behavior in alignment with Islamic principles and standards. Findings: The results indicate a limited number of studies on the successful adoption of the metaverse in HL, HSCM and behavioral research. This paper has proposed a framework for the metaverse-supply chain and halal behavior. The framework can serve as a reference for scholars and practitioners on how to incorporate advanced technology to engage with and predict market demand. Additionally, the metaverse-supply chain framework can be used to align with halal supply chain practices based on customer needs and preferences. The metaverse integrates the virtual world, enabling halal supply chain networks to enhance virtual reality, digital experiences and business performance. Practical implications: The halal industry can showcase products and services through virtual scenarios, avatars and shops. By developing a halal-compliant metaverse, the halal industry can facilitate activities such as online sales, online payments and virtual marketing, thereby enabling a digital business transformation. Embracing the metaverse can improve business efficiency and influence consumer behavior, decisions and compliance with Shariah principles. Originality/value: The authors argue that this paper is at the forefront and will serve as a reference for future research. This paper is distinct from existing literature, as it focuses on metaverse adoption and its correlation with a Shariah compliance framework in logistics, supply chain and behavioral aspects. Through its findings, this framework aims to inspire further empirical research and provide guidance and solutions to foster sustainable development in the halal industry.